The importance of respiration biomechanics and high resolution computed tomography for bronchial-obstructive syndrome diagnostics - E. V. Ekkardt (Бюллетень сибирской медицины, 2010)
The aim of our research was analysis and comparison of chronic obstructive lung disease clinicalsigns and function indices of external respiration apparatus and inspiratory-expiratory high resolution computed tomography. 48 patients with chronic obstructive lung disease were examined. The importance of respiration biomechanics and inspiratory-expiratory high resolution computed tomography indices for diagnostics of broncho-obstruction at an early stage with unchanged forced expiration volume within the first second was revealed.